Expanding the phenotype, genotype and biochemical knowledge of ALG3-CDG. - Alsharhan, Hind; Ng, Bobby G; Daniel, Earnest James Paul; Friedman, Jennifer; Pivnick, Eniko K; Al-Hashem, Amal; Faqeih, Eissa Ali; Liu, Pengfei; Engelhardt, Nicole M; Keller, Kierstin N; Chen, Jie; Mazzeo, Pamela A; et al. (J Inherit Metab Dis, 2021)
Congenital disorders of glycosylation (CDGs) are a continuously expanding group of monogenic disorders of glycoprotein and glycolipid biosynthesis that cause multisystem diseases. Individuals with ALG3-CDG frequently exhibit severe neurological involvement (epilepsy, microcephaly, and hypotonia), ocular anomalies, dysmorphic features, skeletal anomalies, and feeding difficulties. We present 10 unreported individuals diagnosed with ALG3-CDG based on molecular and biochemical testing with 11 novel variants in ALG3, bringing the total to 40 reported individuals. In addition to the typical multisystem disease seen in ALG3-CDG, we expand the symptomatology of ALG3-CDG to now include endocrine abnormalities, neural tube defects, mild aortic root dilatation, immunodeficiency, and renal anomalies. N-glycan analyses of these individuals showed combined deficiencies of hybrid glycans and glycan extension beyond Man GlcNAc consistent with their truncated lipid-linked precursor oligosaccharides. This spectrum of N-glycan changes is unique to ALG3-CDG. These expanded features of ALG3-CDG facilitate diagnosis and suggest that optimal management should include baseline endocrine, renal, cardiac, and immunological evaluation at the time of diagnosis and with ongoing monitoring.

Mutations in GET4 disrupt the transmembrane domain recognition complex pathway. - Tambe, Mitali A; Ng, Bobby G; Shimada, Shino; Wolfe, Lynne A; Adams, David R; Gahl, William A; Bamshad, Michael J; Nickerson, Deborah A; Malicdan, May C V; Freeze, Hudson H (J Inherit Metab Dis, 2020)
The transmembrane domain recognition complex (TRC) targets cytoplasmic C-terminal tail-anchored (TA) proteins to their respective membranes in the endoplasmic reticulum (ER), Golgi, and mitochondria. It is composed of three proteins, GET4, BAG6, and GET5. We identified an individual with compound heterozygous missense variants (p.Arg122His, p.Ile279Met) in GET4 that reduced all three TRC proteins by 70% to 90% in his fibroblasts, suggesting a possible defect in TA protein targeting. He presented with global developmental delay, intellectual disabilities, seizures, facial dysmorphism, and delayed bone age. We found the TA protein, syntaxin 5, is poorly targeted to Golgi membranes compared to normal controls. Since GET4 regulates ER to Golgi transport, we hypothesized that such transport would be disrupted in his fibroblasts, and discovered that retrograde (but not anterograde) transport was significantly reduced. Despite reduction in the three TRC proteins, their mRNA levels were unchanged, suggesting increased degradation in patient fibroblasts. Treating fibroblasts with the FDA-approved proteasome inhibitor, bortezomib (10 nM), restored syntaxin 5 localization and nearly normalized the levels of all three TRC proteins. Our study identifies the first individual with GET4 mutations.

Predominant and novel de novo variants in 29 individuals with ALG13 deficiency: Clinical description, biomarker status, biochemical analysis, and treatment suggestions. - Ng, Bobby G; Eklund, Erik A; Shiryaev, Sergey A; Dong, Yin Y; Abbott, Mary-Alice; Asteggiano, Carla; Bamshad, Michael J; Barr, Eileen; Bernstein, Jonathan A; Chelakkadan, Shabeed; Christodoulou, John; Chung, Wendy K; et al. (J Inherit Metab Dis, 2020)
Asparagine-linked glycosylation 13 homolog (ALG13) encodes a nonredundant, highly conserved, X-linked uridine diphosphate (UDP)-N-acetylglucosaminyltransferase required for the synthesis of lipid linked oligosaccharide precursor and proper N-linked glycosylation. De novo variants in ALG13 underlie a form of early infantile epileptic encephalopathy known as EIEE36, but given its essential role in glycosylation, it is also considered a congenital disorder of glycosylation (CDG), ALG13-CDG. Twenty-four previously reported ALG13-CDG cases had de novo variants, but surprisingly, unlike most forms of CDG, ALG13-CDG did not show the anticipated glycosylation defects, typically detected by altered transferrin glycosylation. Structural homology modeling of two recurrent de novo variants, p.A81T and p.N107S, suggests both are likely to impact the function of ALG13. Using a corresponding ALG13-deficient yeast strain, we show that expressing yeast ALG13 with either of the highly conserved hotspot variants rescues the observed growth defect, but not its glycosylation abnormality. We present molecular and clinical data on 29 previously unreported individuals with de novo variants in ALG13. This more than doubles the number of known cases. A key finding is that a vast majority of the individuals presents with West syndrome, a feature shared with other CDG types. Among these, the initial epileptic spasms best responded to adrenocorticotropic hormone or prednisolone, while clobazam and felbamate showed promise for continued epilepsy treatment. A ketogenic diet seems to play an important role in the treatment of these individuals.

DPAGT1 Deficiency with Encephalopathy (DPAGT1-CDG): Clinical and Genetic Description of 11 New Patients. - Ng, Bobby G; Underhill, Hunter R; Palm, Lars; Bengtson, Per; Rozet, Jean-Michel; Gerber, Sylvie; Munnich, Arnold; Zanlonghi, Xavier; Stevens, Cathy A; Kircher, Martin; Nickerson, Deborah A; Buckingham, Kati J; et al. (JIMD Rep, 2019)
Pathogenic mutations in DPAGT1 cause a rare type of a congenital disorder of glycosylation termed DPAGT1-CDG or, alternatively, a milder version with only myasthenia known as DPAGT1-CMS. Fourteen disease-causing mutations in 28 patients from 10 families have previously been reported to cause the systemic form, DPAGT1-CDG. We here report on another 11 patients from 8 families and add 10 new mutations. Most patients have a very severe disease course, where common findings are pronounced muscular hypotonia, intractable epilepsy, global developmental delay/intellectual disability, and early death. We also present data on three affected females that are young adults and have a somewhat milder, stable disease. Our findings expand both the molecular and clinical knowledge of previously published data but also widen the phenotypic spectrum of DPAGT1-CDG.

Activation of a cryptic splice site in the mitochondrial elongation factor GFM1 causes combined OXPHOS deficiency. - Simon, Mariella T; Ng, Bobby G; Friederich, Marisa W; Wang, Raymond Y; Boyer, Monica; Kircher, Martin; Collard, Renata; Buckingham, Kati J; Chang, Richard; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; et al. (Mitochondrion, 2017)
We report the clinical, biochemical, and molecular findings in two brothers with encephalopathy and multi-systemic disease. Abnormal transferrin glycoforms were suggestive of a type I congenital disorder of glycosylation (CDG). While exome sequencing was negative for CDG related candidate genes, the testing revealed compound heterozygous mutations in the mitochondrial elongation factor G gene (GFM1). One of the mutations had been reported previously while the second, novel variant was found deep in intron 6, activating a cryptic splice site. Functional studies demonstrated decreased GFM1 protein levels, suggested disrupted assembly of mitochondrial complexes III and V and decreased activities of mitochondrial complexes I and IV, all indicating combined OXPHOS deficiency.
Keywords: Child; Child, Preschool; Congenital Abnormalities; Gene Expression; Humans; Infant; Infant, Newborn; Male; Mitochondrial Proteins; Oxidative Phosphorylation; Peptide Elongation Factor G; RNA Splice Sites

Encephalopathy caused by novel mutations in the CMP-sialic acid transporter, SLC35A1. - Ng, Bobby G; Asteggiano, Carla G; Kircher, Martin; Buckingham, Kati J; Raymond, Kimiyo; Nickerson, Deborah A; Shendure, Jay; Bamshad, Michael J; Ensslen, Matthias; Freeze, Hudson H (Am J Med Genet A, 2017)
Transport of activated nucleotide-sugars into the Golgi is critical for proper glycosylation and mutations in these transporters cause a group of rare genetic disorders termed congenital disorders of glycosylation. We performed exome sequencing on an individual with a profound neurological presentation and identified rare compound heterozygous mutations, p.Thr156Arg and p.Glu196Lys, in the CMP-sialic acid transporter, SLC35A1. Patient primary fibroblasts and serum showed a considerable decrease in the amount of N- and O-glycans terminating in sialic acid. Direct measurement of CMP-sialic acid transport into the Golgi showed a substantial decrease in overall rate of transport. Here we report the identification of the third patient with CMP-sialic acid transporter deficiency, who presented with severe neurological phenotype, but without hematological abnormalities.
Keywords: Animals; Brain Diseases; Child; CHO Cells; Cricetinae; Cricetulus; Female; Flow Cytometry; Golgi Apparatus; Humans; Mutation; N-Acetylneuraminic Acid; Nucleotide Transport Proteins; Whole Exome Sequencing

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis

Congenital nephrotic syndrome in an infant with ALG1-congenital disorder of glycosylation. - Harshman, Lyndsay A; Ng, Bobby G; Freeze, Hudson H; Trapane, Pamela; Dolezal, Anna; Brophy, Patrick D; Brumbaugh, Jane E (Pediatr Int, 2016)
Congenital nephrotic syndrome (NS) in the newborn is most frequently related to mutations in genes specific for structural integrity of the glomerular basement membrane and associated filtration structures within the kidney, resulting in massive leakage of plasma proteins into the urine. Occurrence of congenital NS in a multi-system syndrome is less common. We describe the case of an infant with deteriorating neurological status, seizures, edema, and proteinuria who was found to have a mutation in gene ALG1 and a renal biopsy consistent with congenital NS. Furthermore, we briefly review rare existing case reports documenting congenital NS in patients with mutations in ALG1, and treatment strategies, including novel use of peritoneal dialysis.
Keywords: Abnormalities, Multiple; Congenital Disorders of Glycosylation; DNA; DNA Mutational Analysis; Glycosylation; Humans; Infant, Newborn; Male; Mannosyltransferases; Mutation; Nephrotic Syndrome; Peritoneal Dialysis

SRD5A3-CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. - Wheeler, Patricia G; Ng, Bobby G; Sanford, Laura; Sutton, V Reid; Bartholomew, Dennis W; Pastore, Matthew T; Bamshad, Michael J; Kircher, Martin; Buckingham, Kati J; Nickerson, Deborah A; Shendure, Jay; Freeze, Hudson H (Am J Med Genet A, 2016)
Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N-glycosylation, O-mannosylation, C-mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.
Keywords: 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Adult; Child; Congenital Disorders of Glycosylation; Dolichols; Eye; Female; Glycosylation; Homozygote; Humans; Male; Membrane Proteins; Mutation; Phenotype; Skin; Tretinoin

Expanding the Molecular and Clinical Phenotype of SSR4-CDG. - Ng, Bobby G; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J; Wood, Tim; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Wong, Jonathan T S; Monteiro, Fabiola Paoli; Graham, Brett H; Jackson, Sheryl; et al. (Hum Mutat, 2015)
Congenital disorders of glycosylation (CDG) are a group of mostly autosomal recessive disorders primarily characterized by neurological abnormalities. Recently, we described a single CDG patient with a de novo mutation in the X-linked gene, Signal Sequence Receptor 4 (SSR4). We performed whole-exome sequencing to identify causal variants in several affected individuals who had either an undifferentiated neurological disorder or unsolved CDG of unknown etiology based on abnormal transferrin glycosylation. We now report eight affected males with either de novo (4) or inherited (4) loss of function mutations in SSR4. Western blot analysis revealed that the mutations caused a complete loss of SSR4 protein. In nearly all cases, the abnormal glycosylation of serum transferrin was only slightly above the accepted normal cutoff range.
Keywords: Calcium-Binding Proteins; Congenital Disorders of Glycosylation; DNA Mutational Analysis; Exome; Gene Order; Genes, X-Linked; Genetic Loci; Humans; Male; Membrane Glycoproteins; Mutation; Phenotype; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

NGLY1 mutation causes neuromotor impairment, intellectual disability, and neuropathy. - Çağlayan, Ahmet Okay; Comu, Sinan; Baranoski, Jacob F; Parman, Yesim; Kaymakçalan, Hande; Akgümüş, Gözde Tuğce; Caglar, Caner; Dölen, Duygu; Erson-Omay, Emine Zeynep; Harmanci, Akdes Serin; Mishra-Gorur, Ketu; Freeze, Hudson H; et al. (Eur J Med Genet, 2015)
N-glycanase 1 (NGLY1) is a conserved enzyme that is responsible for the deglycosylation of misfolded N-glycosylated proteins in the cytoplasm prior to their proteasome-mediated degradation. Disruption of this degradation process has been associated with various neurologic diseases including amyotrophic lateral sclerosis and Parkinson's disease. Here, we describe two siblings with neuromotor impairment, apparent intellectual disability, corneal opacities, and neuropathy who were found to possess a novel homozygous frame-shift mutation due to a 4 base pair deletion in NGLY1 (c.1533_1536delTCAA, p.Asn511LysfsX51). We hypothesize that this mutation likely limits the capability of neuronal cells to respond to stress due to accumulation of misfolded proteins, thereby impairing their survival and resulting in progressive loss of neurological function.
Keywords: Abnormalities, Multiple; Adolescent; Child; Corneal Opacity; Developmental Disabilities; Female; Frameshift Mutation; Genotype; Humans; Intellectual Disability; Male; Movement Disorders; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Peripheral Nervous System Diseases

A new congenital disorder of glycosylation caused by a mutation in SSR4, the signal sequence receptor 4 protein of the TRAP complex. - Losfeld, Marie Estelle; Ng, Bobby G; Kircher, Martin; Buckingham, Kati J; Turner, Emily H; Eroshkin, Alexey; Smith, Joshua D; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Freeze, Hudson H (Hum Mol Genet, 2014)
Nearly 50 congenital disorders of glycosylation (CDG) are known, but many patients biochemically diagnosed with CDG do not have mutations in known genes. Here, we describe a 16-year-old male who was born with microcephaly, developed intellectual disability, gastroesophageal reflux and a seizure disorder. We identified a de novo variant in the X-linked SSR4 gene which encodes a protein of the heterotetrameric translocon-associated protein (TRAP) complex. The c.316delT causes a p.F106Sfs*53 in SSR4 and also reduces expression of other TRAP complex proteins. The glycosylation marker Glyc-ER-GFP was used to confirm the underglycosylation in fibroblasts from the patient. Overexpression of the wild-type SSR4 allele partially restores glycosylation of the marker and of the other members of the TRAP complex. This is the first evidence that the TRAP complex, which binds to the oligosaccharyltransferase complex, is directly involved in N-glycosylation.
Keywords: Adolescent; Calcium-Binding Proteins; Cells, Cultured; Chromosomes, Human, X; Congenital Disorders of Glycosylation; Glycosylation; Humans; Male; Membrane Glycoproteins; Point Mutation; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

Solving glycosylation disorders: fundamental approaches reveal complicated pathways. - Freeze, Hudson H; Chong, Jessica X; Bamshad, Michael J; Ng, Bobby G (Am J Hum Genet, 2014)
Over 100 human genetic disorders result from mutations in glycosylation-related genes. In 2013, a new glycosylation disorder was reported every 17 days. This trend will probably continue given that at least 2% of the human genome encodes glycan-biosynthesis and -recognition proteins. Established biosynthetic pathways provide many candidate genes, but finding unanticipated mutated genes will offer new insights into glycosylation. Simple glycobiomarkers can be used in narrowing the candidates identified by exome and genome sequencing, and those can be validated by glycosylation analysis of serum or cells from affected individuals. Model organisms will expand the understanding of these mutations' impact on glycosylation and pathology. Here, we highlight some recently discovered glycosylation disorders and the barriers, breakthroughs, and surprises they presented. We predict that some glycosylation disorders might occur with greater frequency than current estimates of their prevalence. Moreover, the prevalence of some disorders differs substantially between European and African Americans.
Keywords: Congenital Disorders of Glycosylation; Exome; Genome, Human; Glucose; Glycogen; Glycosylation; Homeostasis; Humans; Mannose; Mutation

Mosaicism of the UDP-galactose transporter SLC35A2 causes a congenital disorder of glycosylation. - Ng, Bobby G; Buckingham, Kati J; Raymond, Kimiyo; Kircher, Martin; Turner, Emily H; He, Miao; Smith, Joshua D; Eroshkin, Alexey; Szybowska, Marta; Losfeld, Marie E; Chong, Jessica X; Kozenko, Mariya; et al. (Am J Hum Genet, 2013)
Biochemical analysis and whole-exome sequencing identified mutations in the Golgi-localized UDP-galactose transporter SLC35A2 that define an undiagnosed X-linked congenital disorder of glycosylation (CDG) in three unrelated families. Each mutation reduced UDP-galactose transport, leading to galactose-deficient glycoproteins. Two affected males were somatic mosaics, suggesting that a wild-type SLC35A2 allele may be required for survival. In infancy, the commonly used biomarker transferrin showed abnormal glycosylation, but its appearance became normal later in childhood, without any corresponding clinical improvement. This may indicate selection against cells carrying the mutant allele. To detect other individuals with such mutations, we suggest transferrin testing in infancy. Here, we report somatic mosaicism in CDG, and our work stresses the importance of combining both genetic and biochemical diagnoses.
Keywords: Biological Transport; Case-Control Studies; Child; Child, Preschool; Congenital Disorders of Glycosylation; Exome; Female; Glycosylation; Humans; Male; Monosaccharide Transport Proteins; Mosaicism; Mutation; Spectrometry, Mass, Electrospray Ionization; Transferrin; Uridine Diphosphate Galactose